Optimized servo-speed control of wind turbine coupled to doubly fed induction generator - Abdelhamid Mansouri; Fateh Krim (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Optimal control of any variable speed wind turbine needs maximum power point tracking (MPPT) coupled to doubly fed induction generator (DFIG) for better power generation. This paper offers a novel direct power servo-speed control of wind turbine. This latter is based on DFIG optimal hysteresis MPPT inverter current control combined with space voltage modulation (SVM) inverter voltage technique, thus providing a stable and continuous energy flow to power grid. In this design, the asynchronous machine stator is directly connected to the grid. Bidirectional power converter, acting as frequency converter, is rotor circuit located. Rectifier supplies rotor windings with voltages and reference frequency resulting from control procedure of the power exchange between the stator and grid. Inverter is directly controlled by means of SVM technique to maintain direct current (DC) bus voltage constant. Simulation results show that the proposed configuration improves power converters efficiency due that rotor circuit needs less power than stator circuit which is injected into the grid.